Astragalus mongholicus Bunge and Panax Notoginseng Formula (A&P) Combined With Bifidobacterium Contribute a Renoprotective Effect in Chronic Kidney Disease Through Inhibiting Macrophage Inflammatory Response in Kidney and Intestine - Rui-Zhi, Tan; Hui, Diao; Jian-Chun, Li; Xia, Zhong; Xiao-Jia, Wang; Dan, Wen; Jun-Ming, Fan; Li, Wang (Frontiers in Physiology, 2020)
There is increasing evidence that Chronic Kidney Disease (CKD) can cause intestinal dysfunction, which in turn aggravates the progression of kidney disease. Studies have shown that the immune response of macrophage plays an important role in promoting inflammation in kidney and intestine of CKD. Astragalus mongholicus Bunge and Panax notoginseng formula (A&P) is a widely used traditional medicine for the treatment of CKD in China, however, the underlying mechanism is largely unclear. In this study, we aimed to explore the role of A&P and Bifidobacterium combination treatment in regulation of inflammatory response of macrophage in kidney and intestine of CKD mouse, as well as the potential molecular mechanism. We established a CKD mouse model with 5/6 nephrectomy and a macrophage inflammatory cellular model with LPS and urotoxin in vivo and in vitro. The results showed that A&P combined with Bifidobacterium significantly reduced the expression and secretion of IL-1β, IL-6, TNFα and MCP-1 in kidney, intestine and blood, as well as in inflammatory macrophage. Interestingly, A&P combined with Bifidobacterium strongly improved the intestinal flora and protected the intestinal barrier. Notably, the maintainer of macorphage polarization, Mincle, was activated in kidney and intestine of CKD mouse as well as in urotoxin stimulated macrophage, that was effectively inhibited by treatment of A&P and Bifidobacterium combination. Overexpression of Mincle by genetic modification can abolish the inhibitory effects of A&P combined with Bifidobacterium on inflammation in urotoxin stimulated RAW264.7 cells. In summary, these findings demonstrated that A&P combined with Bifidobacterium can protect kidney against CKD by down-regulating macrophage inflammatory response in kidney and intestine via suppressing Mincle signaling, which provides a new insight in treatment of CKD with traditional medicine.